2007
DOI: 10.1245/s10434-007-9462-0
|View full text |Cite
|
Sign up to set email alerts
|

Critical Analysis of Treatment Failure After Complete Cytoreductive Surgery and Perioperative Intraperitoneal Chemotherapy for Peritoneal Dissemination From Appendiceal Mucinous Neoplasms

Abstract: The present study reported the patterns of treatment failure after complete cytoreduction and demonstrated that a disease-free state is important for long-term survival in peritoneal dissemination from appendiceal mucinous neoplasms. Repeat complete cytoreduction should be pursued when possible and is associated with improved overall survival in patients with recurrent disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 18 publications
3
77
0
5
Order By: Relevance
“…It has been clearly demonstrated that a combined approach of CRS and HIPEC is the standard treatment of patients with PPM because it is able to provide a survival advantage compared with historical controls. Treatment failure may be predicted by several prognostic factors, which were validated in large series [6,[16][17][18]. Several retrospective analyses documented that previous use of systemic chemotherapy was an independent poor prognostic factor for patients undergoing curative CRS and HIPEC for appendiceal neoplasms associated with PPM [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…It has been clearly demonstrated that a combined approach of CRS and HIPEC is the standard treatment of patients with PPM because it is able to provide a survival advantage compared with historical controls. Treatment failure may be predicted by several prognostic factors, which were validated in large series [6,[16][17][18]. Several retrospective analyses documented that previous use of systemic chemotherapy was an independent poor prognostic factor for patients undergoing curative CRS and HIPEC for appendiceal neoplasms associated with PPM [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…In some patients the cancer remains confined to the abdomen and pelvis throughout the natural history, consequently multiple reoperations can result in benefit [2,3]. Also, more often than not, these patients may come to a definitive surgical intervention having had several prior unsuccessful debulking procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Extent of the prior surgeries, high peritoneal cancer index (PCI) (31), elevated levels of CA19-9 (32) and CEA (33) were identified as poor prognostic factors by multivariate analysis. Peritoneal recurrence of PMP occurs as a result of the advanced stage of the disease at the time of initial diagnosis or as the consequence of relative chemoresistance to chemotherapy.…”
Section: Pseudomyxoma Peritoneimentioning
confidence: 99%